Post-traumatic Growth Level and Its Influencing Factors Among Frontline Nurses During the COVID-19 Pandemic - Peng, Xin; Zhao, Hui-zi; Yang, Yi; Rao, Zhen-li; Hu, De-ying; He, Qin (Frontiers in Psychiatry, 2021)
Objective To understand the levels of post-traumatic growth in front-line nurses after the COVID-19, and analyze the reasons and influence factors. Methods The general information of the front-line nurses and the post-traumatic growth inventory (PTGI) were used to carry out the cross- sectional study in 116 nurses who took part in the COVID-19. Results The average score of PTGI in front-line nurses was ( 65.647±11.498 ) points.The results of single factor analysis showed that : gender, age, education level, marital status, living with parents, professional title, working years and professional psychological support has no statistical significance in the growth scores of the front-line nurses（P>0.05）. The scores : health status, had children, supported by family members and friends,has statistical significance in the growth scores of the front-line nurses（P<0.05）. Multiple linear regression analysis showed that health status, had children, supported by family and friends could increase the total score of PTGI. All the variables could explain 3.8% variance of post-traumatic growth. Conclusion Front-line nurses have higher post-traumatic growth at the early stage of the epidemic, reasonable deployment of human resources, attention to the physical and mental health of the nurses, strong social support and professional psychological intervention can help the front-line nurses get better post-traumatic growth. It is still necessary to carry out longitudinal observation on the front-line nurses after the epidemic.